2023
DOI: 10.1097/yco.0000000000000861
|View full text |Cite
|
Sign up to set email alerts
|

Dementia among older people with schizophrenia: an update on recent studies

Abstract: Purpose of reviewThis narrative review examines recently published research that examines the prevalence, underlying causes, and treatments for dementia among people with schizophrenia.Recent findingsPeople with schizophrenia have high rates of dementia, compared with the general population, and cognitive decline has been observed 14 years prior to onset of psychosis with accelerated decline in middle age. Underlying mechanisms of cognitive decline in schizophrenia include low cognitive reserve, accelerated co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…This set includes several interesting phenotypes such as "tobacco use disorder," "diabetes" and "dementias" where prior work has implicated genetic sharing and similar etiologies. [70][71][72][73][74][75] Our results would suggest that the genetic risk of schizophrenia is not the primary contributing factor to these comorbidities supporting other potential hypotheses and with potential for intervention. In fact, these results indicate that genetic risk of schizophrenia decreases risk of diabetes despite very high comorbidity providing an even stronger case for other contributors such as medication.…”
Section: Discussionsupporting
confidence: 73%
“…This set includes several interesting phenotypes such as "tobacco use disorder," "diabetes" and "dementias" where prior work has implicated genetic sharing and similar etiologies. [70][71][72][73][74][75] Our results would suggest that the genetic risk of schizophrenia is not the primary contributing factor to these comorbidities supporting other potential hypotheses and with potential for intervention. In fact, these results indicate that genetic risk of schizophrenia decreases risk of diabetes despite very high comorbidity providing an even stronger case for other contributors such as medication.…”
Section: Discussionsupporting
confidence: 73%
“…Even for the most significant PRS associations among this set, the effect sizes are quite small (variance explained < 0.5%), potentially pointing to nongenetic causes as primary drivers of comorbidities. This set includes several interesting phenotypes such as tobacco use disorder, diabetes, and dementias, where prior work has implicated genetic sharing and similar etiologies ( 78 , 79 , 80 , 81 , 82 , 83 ). Our results suggest that the genetic risk of schizophrenia is not the primary contributing factor to these comorbidities, supporting other potential hypotheses and with potential for intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our findings of multivariate adjusted ORs showed that a clinical history of schizophrenia 5 and 10 years ago was related to an increased incidence of dementia. Recent studies have demonstrated rapid cognitive decline and brain changes in middleaged and older individuals with schizophrenia compared to healthy individuals [36].…”
Section: Discussionmentioning
confidence: 99%